Biopsychosocial problems experienced by menopausal women - Savitha P Cutinho; Flora D'Souza; Shirley P D'Souza; Iona D D'Costa; Sindhu Sebastian; Alphilin Jose (Wolters Kluwer Medknow Publications, 2013)
Objectives: The aim of this study is to assess the selected biopsychosocial problems of menopausal women; to explore the relationship between the biological, psychological, and social problems associated with menopause; and to find an association between the biopsychosocial problem and the selected baseline variables. Materials and Methods: A descriptive study conducted among 50 postmenopausal women in Father Muller Medical College Hospital, from November 2011 to January 2012. The purposive sampling technique was used to select 50 postmenopausal women. Data was collected using a rating scale on biopsychosocial problems. Results: The biopsychosocial problems experienced by the women at moderate levels: Most of the postmenopausal women experienced biological problems. The problems were ranked based on the percentage. Conclusion: The finding of the study implicates that biological problems are felt the most in comparison with the psychological and social problems.